Managing Malaysian water resources development - Mohd. Azhar, G. (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2000)
Water is a gift of God and Malaysia is rich in water resources. Water development has fueled socio-economic development of the country during the past decades.Dams and thousands of kilometres of pipes and canals divert water from the rivers to sustain domestic, industrial and agricultural needs. Lately, the water situation for the country has changed from one of relative abundance to one of relative scarcity.The population growth and the expansion in urbanisation, industrialisation and irrigated agriculture are imposing rapidly growing demands and pressure on the water resources, besides contributing to the rising water pollution. Water management is becoming increasingly comprehensive and complicated due to larger concentrations of population, commercial activities and industries around the cities and towns, increasing water consumption, increasing water pollution, increasing land use conflicts and climate changes. At the same time, development of new water resources to meet the ever increasing water demand is facing opposition from the environmentalists. Therefore, the preferred water supply management approach,whereby new supply sources are tapped to meet increasing demand should be replaced by water demand management approach, whereby efforts are directed towards managing the demand to keep it within available supply sources. Water demand management monitors and improves the efficiency of the supply system and all water users need to adjust their needs to the available water. The way forward to a prosperous and sustainable future is by keeping development to a level that is kept within the carrying capacity of the river basin while protecting and restoring the environment. As such, the water demand management should be practised within the broader context of integrated water resources management (IWRM). IWRM is an approach towards integrating and effectively coordinating policies, programs and practices addressing the water related issues which takes into consideration the aspects of socio-economic development and the conservation of the environment. The comprehensive management of water resources will cover three components namely,the management of water as a precious resource, the management of wastewater and water pollution, and the management of water related hazards such as floods, droughts and landslides. Whilst water related problems are essentially local issues,the solutions to such problems must be tackled from a broader perspective. These will require improved professional capability, and increased financial, legislative,managerial and political capacity.